PROSPEK GAGAL SUKSES PINJAMAN UMKM MELALUI PEER-TO-PEER LENDING PADA LENDINGCLUB - Wibi Andriansyah; Agung Winarno (Ekonomi Bisnis, 2019)
Peer-to-peer lending as an innovation of financial services is a genuine opportunity for SMEs who are experiencing difficulties in accessing loans to formal financial institutions. The asymmetric information issue on peer-to-peer lending activity can lead to a credit risk that may cause a default loan. This research is a kind of associative research with the form of causal relationship. the purpose of this study is to determine the factors that influence the success of SMEs loans on Peer to peer lending activities. Samples obtained from the LendingClub platform using purposive sampling method. Analysis In this study using logistic regression analysis. Based on logistic regression analysis, it is found that loan amount, loan term, debt-to- income ratio, delinquency in last 2 year, inquiries in the last 6 month, and revolving credit utilization have a significant negative effect on the success of the loan. while annual income is not significant effect on the success of the loan.